Answer:
![x_1=(1)/(5)+(√(29))/(5)i\\x_2=(1)/(5)-(√(29))/(5)i](https://img.qammunity.org/2020/formulas/mathematics/middle-school/pfim5uth9pro6neyks3l6p1t81hk9oxdzp.png)
Explanation:
1. You can solve the quadratic equation by completing the square, as following:
- The leading coefficient must be 1, therefore, you need to divide the equation by 5:
![(5x^(2)-2x+6)/(5)=0\\x^(2)-(2)/(5)x+(6)/(5)=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jpf9kh7o9n9oqqv233cxntlsn0wywvj2dw.png)
- Substract
at both sides:
![x^(2)-(2)/(5)x+(6)/(5)-(6)/(5)=-(6)/(5)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/sofzu6ayxqcmo5g7ix10ln5s2h0jicgvui.png)
![x^(2)-(2)/(5)x=-(6)/(5)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lea6dh37kxpp10io1goklr9c3iosrf3520.png)
- Divide the coefficient of
by 2 and and square it:
![((2)/((5)/(2)))^(2) =(1)/(25)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/wg9u6ai6ivuirn6goddumg8ldiwipavkg1.png)
- Add it to both sides:
![x^(2)-(2)/(5)x-(1)/(25)=-(6)/(5)+(1)/(25)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/rd2mgk297cxjk070kbhk6rojq3hpc2f6za.png)
- Then:
![(x-(1)/(5))^(2) =-(29)/(25)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/g056xgtt91wn5hmjl0kymt5vh2tz82luca.png)
![x-(1)/(5)=\sqrt{-(29)/(25)}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ykiszjs8q7a0phojmitdg4g5gcgim9q8ga.png)
- Knowing that
:
![x_1=(1)/(5)+(√(29))/(5)i\\x_2=(1)/(5)-(√(29))/(5)i](https://img.qammunity.org/2020/formulas/mathematics/middle-school/pfim5uth9pro6neyks3l6p1t81hk9oxdzp.png)